Community-Based First Aid Education for Out-of-Hospital Asthma Attack Management among Laypersons - Fakrul Ardiansyah; Sudarto Sudarto; Halina Rahayu; Azhari Baedlawi; Hieronimus Amandus; Vitria Handayani; Eli Saripah (Jurnal Pengabdian Masyarakat Lentora, 2026)
Airway inflammation, obstruction, and bronchial hyperresponsiveness characterise asthma in children and young adults. Data shows that 38 asthma patients died due to delays in emergency referral, difficulties in initial care, and classroom teachers' incompetence to treat asthma attacks. This Community Service Program teaches SMAN 1 Sungai Ambawang Asthma First Aid. Asthma First Aid teaching at SMAN 1 Sungai Ambawang is essential for community asthma treatment independence. This project attempts to improve asthma attack quality of life. Community service uses lectures, Q&As, and demonstrations. Students, instructors, and the SMAN 1 Sungai Ambawang School Health Unit (UKS) Team will engage in this community service. There are 50 participants. To start community service, follow these steps. Pre-tests are 16 questions and take 16 minutes. The team then teaches asthma first aid for one hour. Steps for first aid are demonstrated. Participant practise what they learned. Following the test, they have 16 minutes to complete a 16-question questionnaire. The pretest-posttest analysis shows that participants learned asthma first aid. Community service can increase asthma attack prevention knowledge. The public health center and education office should increase asthma first aid education. To avoid asthma attacks, SMAN 1 Sungai Ambawang students and community members need regular education.